Archipelagic Consciousness: Reimagining National Identity Through Local and Maritime Histories in Indonesian Primary Education - Firzan Dahlan; Grace Freya Purba; Farah Faiza; Amir Serikova; Danila Adi Sanjaya; Yuniarti Maretha Pasaribu; Susi Diana; Christian Napitupulu; Maya Enderson; Emir Abdullah (Enigma Institute, 2025)
The formation of national identity in Indonesia, the world's largest archipelagic state, has historically been dominated by a centralized, terrestrial-focused historical narrative that often marginalizes the rich diversity of local and maritime histories. This study addressed the gap in understanding how a pedagogical shift towards these histories could foster a more inclusive and interconnected sense of nationhood, termed 'Archipelagic Consciousness', among young learners. A quasi-experimental, mixed-methods study was conducted over one academic semester in four primary schools across Indonesia. A total of 180 fifth-grade students participated, divided into an experimental group and a control group. The experimental group received a pedagogical intervention based on local hero narratives, inter-island trade routes, and project-based learning focused on maritime culture. Data were collected using a validated pre-test/post-test 'Archipelagic Consciousness Inventory' (ACI), supplemented by qualitative data from focus group discussions and student portfolio analysis. Quantitative data analysis revealed a statistically significant, large-effect-size improvement in the ACI scores for the experimental group compared to the control group. Qualitative findings corroborated these results, with major themes emerging that included the validation of local identity as integral to the national story, a conceptual shift from viewing the sea as a barrier to a connector, and an enhanced appreciation for inter-regional cultural diversity. In conclusion, the pedagogical model centered on local and maritime histories was highly effective in cultivating Archipelagic Consciousness. Integrating these narratives into primary education offers a potent pathway for reimagining Indonesian national identity as a dynamic, interconnected, and pluralistic tapestry, moving beyond a monolithic, land-based conception. This study provides empirical support for curriculum reform aimed at fostering a more resilient and inclusive national identity.